Review of Cost Management Strategies in Engineering Projects: Balancing Budget and Quality - Mohammadi, Ebrahim (Management Strategies and Engineering Sciences, 2021)
Cost management is a critical component in the successful execution of engineering projects, where balancing budget constraints with maintaining high-quality standards presents a significant challenge. This narrative review synthesizes existing literature on cost management strategies in engineering projects, focusing on how these strategies effectively address the dual objectives of cost control and quality assurance. The review covers fundamental principles of cost management, including cost estimation, budgeting, and cost control, and discusses the trade-offs between budget limits and quality standards. Key strategies such as earned value management, life cycle costing, value engineering, and risk management are explored through case studies, highlighting both successful applications and instances where cost management failed, leading to budget overruns or compromised quality. A comparative analysis of cost management practices across different sectors, project scales, and geographical regions is also presented. The findings underscore the importance of accurate cost estimation, proactive cost control, and the integration of advanced technologies to enhance cost management practices. The review concludes by identifying gaps in current knowledge and suggesting areas for future research, particularly in the development of more sophisticated cost management models that incorporate emerging technologies.